PENGARUH GAME EDUKASI DIGITAL TERHADAP KEMAMPUAN PROBLEM SOLVING ANAK PAUD - Yunita; Putri Jannah Aulia; Irsa; Wanur Khadillah; Fadhilah Syam Nasution (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aimed to determine the effect of digital educational games on early children’s problem-solving skills aged 4–5 years. The study employed a quantitative approach using a quasi-experimental method with a One Group Pretest–Posttest Design. The participants consisted of 20 kindergarten students in group B. Data were collected through observation and documentation and analyzed using a paired sample t-test with the assistance of IBM SPSS Statistics. The findings showed an improvement in children’s problem-solving skills after the implementation of digital educational games. The mean pretest score increased from 61.25 to 84.10 in the posttest. The hypothesis testing revealed a significance value of 0.000 (p < 0.05), indicating that digital educational games had a significant effect on kindergarten children’s problem-solving skills. Therefore, digital educational games can be used as an innovative learning medium to support young children’s cognitive development.